Pengaruh Perencanaan Pajak Dan Beban Pajak Tangguhan Terhadap Manajemen Laba Dengan Good Corporate Governance Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2021 - Ardisa Dewi Rahmanjani; Mulyadi Mulyadi; Panata Bangar Hasioan Sianipar (Akuntansi, 2023)
This study aims to: (1) Estimating and testing the impact of tax planning on earnings management; 2. Estimating and testing the influence of deferred tax expenses on earnings management; (3) The estimation and analysis of Good Corporate Governance can act as a moderating factor in the relationship between tax planning and earnings management. (4) Good Corporate Governance may help predict and analyze the impact of deferred tax cost on profits management. This study employs quantitative methods. Secondary data in the form of annual reports of manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021 are utilized in this research. Purposeful sampling was employed for this study. The study's findings suggest that: (1) Tax planning demonstrates a partial or independent influential impact on earnings management. (2) The effect of deferred tax expense on earnings management is not statistically significant, either in part or individually. (3) Good Corporate Governance acts as a moderating factor in the relationship between tax planning and earnings management; (4) Good Corporate Governance plays a moderating role in the relationship between deferred tax expense and earnings management.